2008
DOI: 10.1007/s10745-007-9154-1
|View full text |Cite
|
Sign up to set email alerts
|

Farm Households and Land Use in a Core Conservation Zone of the Maya Biosphere Reserve, Guatemala

Abstract: This paper employs cross-tabular analysis, and multivariate and logistic regression to explore demographic, political-economic, socioeconomic, and ecological patterns of farm households and land use outcomes in an emergent agricultural frontier: the Sierra de Lacandón National Park (SLNP)-a core conservation zone of the Maya Biosphere Reserve (MBR), Petén, Guatemala. Data were obtained from a 1998 probability sample of 241 farm households, the first large detailed household land use survey in Guatemala's Selva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 59 publications
2
29
1
Order By: Relevance
“…Future research and policies must be particularly responsive to social dynamics underlying land use management systems. The role of migration and other adaptive strategies of farmers (Carr 2008), which could have an effect on decisions related to practices that enhance biodiversity have to be understood and taken into account. …”
Section: Discussionmentioning
confidence: 99%
“…Future research and policies must be particularly responsive to social dynamics underlying land use management systems. The role of migration and other adaptive strategies of farmers (Carr 2008), which could have an effect on decisions related to practices that enhance biodiversity have to be understood and taken into account. …”
Section: Discussionmentioning
confidence: 99%
“…Beyond its impact on the selection of diversification and saving adaptation strategies, the scholarship on land-use change has found that distance is a critical factor for deforestation (Nagendra et al 2006, Bray et al 2008, Carr 2008. Proximity to commercial and administrative centers creates more opportunities for people to commercialize their agricultural products, send their children to school and network with farmers from different communities and governmental and nongovernmental organizations, which expand farmers' horizons beyond landintensive activities.…”
Section: Distance Cash Benefits and Deforestation-driving Adaptatiomentioning
confidence: 99%
“…However, there are still knowledge gaps, especially in the relationships between and among the biophysical, economic development, sociocultural aspects, and effective policy responses (Carr 2008;Chomitz et al 2007;Damnyag et al 2013;Mattsson et al 2012;Pasgaard 2013;Pouliot et al 2012). Moreover, most studies of deforestation drivers have been based on macrolevel regional or national data, thus presenting difficulties in addressing the complexity of local situations (Bottazzi and Dao 2013).…”
mentioning
confidence: 99%